2020
DOI: 10.1103/physrevb.102.045309
|View full text |Cite
|
Sign up to set email alerts
|

Spiraling vortices in exciton-polariton condensates

Abstract: We introduce the phenomenon of spiraling vortices in driven-dissipative (nonequilibrium) exciton-polariton condensates excited by a nonresonant pump beam. At suitable low pump intensities, these vortices are shown to spiral along circular trajectories whose diameter is inversely proportional to the effective mass of the polaritons, while the rotation period is mass independent. Both the diameter and rotation period are inversely proportional to the pump intensity. Stable spiraling patterns in the form of compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In atomic BEC, the loss of particles may cause vortices to spiral towards regions where they vanish [61,62]. Spiraling vortices have also been observed in non-equilibrium polariton BECs, such as those pumped by a broad super-Gaussian beam with a flat-top [63], as well as for continuous-wave pump [64]. In the present case of a circular beam P(r) = ηP th Θ(R p − r), spiraling vortices are discovered from the spiraling phase distributions.…”
Section: Dynamical Evolutionmentioning
confidence: 97%
“…In atomic BEC, the loss of particles may cause vortices to spiral towards regions where they vanish [61,62]. Spiraling vortices have also been observed in non-equilibrium polariton BECs, such as those pumped by a broad super-Gaussian beam with a flat-top [63], as well as for continuous-wave pump [64]. In the present case of a circular beam P(r) = ηP th Θ(R p − r), spiraling vortices are discovered from the spiraling phase distributions.…”
Section: Dynamical Evolutionmentioning
confidence: 97%
“…A similar sequence of time delayed pulses has been used to shape nonlinear processes of high harmonic generation, resulting in a * a.rahmani.mir@gmail.com time-varying OAM 11 . Also, external potentials can generate rotating wavepackets; model examples are harmonic potential 12 and ring shaped potential 13,14 where the angular content is constant, or spiraling vortices can emerge from the sudden switch of a continuous-wave ring beam 15 .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, using the natural filtering of the full-wavefunction offered by the cavity photoluminescence, rather than using a polarization filtering, the Bloch singularity was directly projected into the helicoidal dynamics of a vortex line sculpted into the light emission from the system. Full-Bloch beams hosting Rabi-spiraling vortices are also endowed with time-varying orbital angular momentum (OAM), similarly to those recently generated through nonlinear phenomena 51,52 . One way to understand such structured emission is in terms of the mechanics found by Nye and Berry 1,53 , who showed that photonic helical dislocations in 3D space can be ascribed to the superposition of straight vortex lines with, e.g., a tilted plane wave, and to their continuously varying relative phase, due to different wavevector directions.…”
Section: Introductionmentioning
confidence: 99%